Evaluasi Kesuksesan dan Keberterimaan Sistem Informasi Anggaran PT. PLN (PERSERO) - Andi Nurul Istiyana (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2020)
The success of information systems is one thing that needs to be evaluated. Not only the success, but the acceptance of information systems by users also need to be considered. However, some of these studies do not pay attention to the nature of system use is mandatory or voluntary. The considerable implementation costs and expected results are a consideration of why this evaluation needs to be done. Data collection was done by distributing questionnaires to budget employees of PT PLN (PERSERO). In this research will be tested the success of information system by using DeLone and Mclean success model (1992), then add testing to system acceptance by using perception of usage and perception of ease of use from model of acceptance developed by Davis (1989). The use of compulsory systems is a consideration for combining the two models. The results show that the budget system is successfully applied to PLN but there are some obstacles and there is no effect of the usability of the perception and ease of use of perception on the system because the system is mandatory